Mythologies of Roland Barthes - Acetoso, Mattia (Romance eReview, 2017)
On November 13-14, 2015, the graduate students of the Department of Romance Languages and Literatures at Boston College organized an academic conference in honor of Roland Barthes (1915-1980). In commemoration of the French critic’s centennial, scholars from all over the country gathered in Stokes Hall for two days of discussions and intellectual exchange. This monographic issue of Romance eReview seeks to capture the energy and liveliness of our graduate conference. These notes from the editor offer details about the conference and the articles of this issue of the journal.